Sensor de NO2 utilizando-se filmes moleculares de macrociclos de porfirinas - Nelicio Faria de Sales (2009)
The object of this work is the study, characterization and development of new sensors using the LB and LS of thin films deposition techiniques. Such sensors has been used for the gas sensing of NO2, althought, not discarting its use for detecting other gases or substances such as alchools or herbicides, etc. The materials used for assemble thesensors were the 5,10,15,20-tetraphenyl-21H,23H-porphine (H2TPP) and its derivative with the cobalto at center, Cobalt 5,10,15,20 meso-tetraphenyl porphyrin (CoTPP). We have evaluated the infuence of concentration of 5,10,15,20-tetraphenyl-21H,23H porphine solutions on -A isotherms, varing the pH of subphase. The obtained -Aisotherms indicated the existence of different aggregation states and the dependence of area/molecule with the pH was established. There is an increase in the area/molecule for both pH=5 and pH=8 in low concentrations with a marked increase for the acid pH. Such trend has given such clearly evidence that proton (H+) effect in the chromophore macrocycle is potentially indicated for the pH-sensitive gas sensors. The sensitivity of 5, 10, 15, 20-tetraphenylporphyrin (H2TPP) to the presence of NO2 gas in diluted solutions and in Langmuir-Blodgett (LB) and Langmuir-Schaefer (LS) films was investigated by UV-visible spectroscopy. The shift of Soret and Q bands were analyzed and the energies involved were calculated. The exposure of LB porphyrinfilms deposited onto glass slides to NO2 has performed as an active chemsensor with 7000 ppm gas concentration. Furthermore, the UV-vis dichroism absorption results associated with the Soret bands have given evidence of the tilt angle of the macrocycle related to the substrate. H2TPP in LB film was tilted by an angle of 51 5and in the LS film was tilted by an angle of 365indicating the formation of a preferentialorganization of the molecular films depending on the deposition method.